Status of Coral Reef Benthic Cover in the Gili Balu Marine Conservation Area, Sumbawa, West Nusa Tenggara - Himawan, Mahardika Rizqi; Santana, Lalu Bagus; Lestariningsih, Wiwid Andriyani; Hidayatullah, Rahmat; Prabuning, Derta (Jurnal Biologi Tropis, 2024)
The coral reef ecosystem in Indonesia boasts the highest biodiversity and serves as the center of the Coral Triangle's diversity. Despite its richness, Indonesia's coral reefs face increasing threats from various factors, primarily anthropogenic. Regular biophysical surveys of coral reef ecosystems are therefore necessary to monitor their current conditions and guide management efforts. This study aimed to assess the condition of coral reefs by examining the percentage of coral cover in the Gili Balu Marine Conservation Area, Sumbawa NTB. The research was conducted in January, 2022, using the Point Intercept Transect (PIT) method at 10 observation points. The transects measured 50 meters in length and were repeated three times at each location. The results indicated that the coral reefs were in good condition at the South Belang Island Station (57%) and West Pasareang Island (69.67%), according to Kepmen LH No. 4/2001. However, moderately damaged reefs were observed at North Belang Station (38%), Kenawa Island (30%), East Belang Island (30%), and Mandiki Island (28.67%). Coral reefs classified as severely damaged were found at Southwest Namo Island Station (17.33%), North Pasareang (16.67%), South Kalong (11%), and North Namo (9.67%). Overall, the dominant condition of coral reefs in the Gili Balu Conservation Area was categorized as moderately to severely damaged. Conservation efforts, including protection in areas with good conditions and rehabilitation in damaged areas, are recommended as follow-up actions to support coral reef sustainability in Gili Balu.